Influence of supplier management on the implementation of effective procurement practices in tertiary public training institutions in Kenya - Njeru, Silas E.; Arasa, Robert; Ngugi, Patrick; Kahiri, James (Issues in Business Management and Economics, 2014)
In Kenya, over 70% of tertiary public training institutions procurement practices are normally not in full compliance with Public Procurement and Disposal Act, 2005 and Public Procurement and Disposal Regulations, 2006 (Joseph, 2010). In over 50% of tertiary public training institutions, the quality and quantity of procured good and services does not meet the raised specifications during tendering. There are several stalled development projects and the actual procurement expenditure is normally higher than the budgeted procurement funds. Supplier management concept is increasingly being embraced towards enhancing effective implementation of programmes and realization of expected goals. This study set out to establish the influence of supplier management on implementation of effective procurement practices in tertiary public training institutions in Kenya. The study employed a descriptive research designs.The study population comprised of a total of 320 procurement staff in procurement departments of all the 40 tertiary public training institutions in Kenya. A stratified random sampling technique was employed to select a sample size of 160 respondents. The main data collection instruments used included questionnaires containing open ended and closed ended questions with the quantitative section of the instrument utilizing both a nominal and a Likert-type scale format.The study findings shows that supplier management factors such as supplier appraisal techniques, supplier selection strategies, supplier selection process, supplier performance methods, supplier relationship management, supplier development and supplier collaboration to a large extent influenced implementation of effective procurement practices in many tertiary public training institutions. The study recommends that managers of tertiary public training institutions should embrace effective supplier management strategies, effective supplier appraisal techniques, better supplier selection strategies, effective supplier selection process, better supplier performance methods, effective supplier relationship management techniques,supplier development and supplier collaboration initiatives
Keywords: Supplier management; Effective procurement practices; Tertiarypublic training institutions